Study of fruit and vegetable intake in breast cancer patients in the city of Sabzevar - Akram Kooshki; Manidgeh Yousefi Moghaddam; Roya Akbarzadeh (Electronic Physician, 2016)
Introduction: Diet is one of the most important modifiable risk factors for prevention and control of chronic diseases, including breast cancer. This study aimed to determine the fruit and vegetable intake in women with cancer breast in Sabzevar. Methods: This cross-sectional study was conducted on 125 women with breast cancer in Sabzevar in 2011. Census sampling was done on volunteers in a visiting home and suspected women referred to the mammography, ultrasound, and radiology clinic in the Sabzevar center for breast cancer. Demographic and semi quantitative food questionnaires of 160 foods were completed for each of the patients by trained interviewers. Data were analyzed using the software Nutritionist IV. Descriptive statistics, one-sample t-test, and Chi-square test were used, employing the SPSS version 16. Results: In this study, 125 women were assessed with breast cancer. The highest risk with breast cancer was 35.5% in women 40 to 49 years old. The results of this study showed that patients with breast cancer had minimum daily recommended intake (3.06 ± 2.3 serving of fruits and 2.09 ± 1.81 serving of vegetables in days). One sample t-test showed that the mean intake of fruits and vegetables was not a significant deference with daily recommended intake (p>0.05). The chi-square test showed that patients with minimum daily recommended intake of fruits and vegetables were at high risk for breast cancer in comparison with those who received the highest amount (p=0.001). Conclusion: This study supports evidence that high vegetable and fruit intake is associated with lower breast cancer risk.